Purification and Structural Study of the Voltage-Sensor Domain of the Human KCNQ1 Potassium Ion Channel - Peng, Dungeng (American Chemical Society, 2014)
[Image: see text] KCNQ1 (also known as K(V)7.1 or K(V)LQT1) is a voltage-gated potassium channel modulated by members of the KCNE protein family. Among multiple functions, KCNQ1 plays a critical role in the cardiac action potential. This channel is also subject to inherited mutations that cause certain cardiac arrhythmias and deafness. In this study, we report the overexpression, purification, and preliminary structural characterization of the voltage-sensor domain (VSD) of human KCNQ1 (Q1-VSD). Q1-VSD was expressed in Escherichia coli and purified into lyso-palmitoylphosphatidylglycerol micelles, conditions under which this tetraspan membrane protein yields excellent nuclear magnetic resonance (NMR) spectra. NMR studies reveal that Q1-VSD shares a common overall topology with other channel VSDs, with an S0 helix followed by transmembrane helices S1–S4. The exact sequential locations of the helical spans do, however, show significant variations from those of the homologous segments of previously characterized VSDs. The S4 segment of Q1-VSD was seen to be α-helical (with no 3(10) component) and underwent rapid backbone amide H–D exchange over most of its length. These results lay the foundation for more advanced structural studies and can be used to generate testable hypotheses for future structure–function experiments.